Perancangan Sistem Informasi Pendaftaran Perserta Didik Baru di SMK AZ ZAHRA SEPATAN Berbasis Web Dengan Metode Waterfall - Wahyu Candra Wijaya; Kecitaan Harefa (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
SMK AZ ZAHRA SEPATAN currently still has several shortcomings in accepting new students, namely prospective students must come to the school to carry out registration directly to the school, fill out the form with paper and pen and submit supporting files to the committee, then the candidates Students still have to return to school to find out the announcement and results of the eligibility selection for students accepted at SMK AZ ZAHRA SEPATAN, besides that, the committee must validate files and sort out the eligibility of prospective students based on test scores. school, then make a list of students who pass the selection by sticking it on the school wall. This method is considered less effective because it can cause various problems, one of which is that files are often lost or lost. With this method, several problems arise, including taking up time and energy, PPDB committee members still often have difficulty reading students' handwriting if the handwriting is not clear. . Prospective students still have to return to school to find out about the announcement and results of the eligibility selection for students accepted at SMK AZ ZAHRA SEPATAN.